Analyzing Tuberculosis Disease in Martubung Village District Medan Labuhan - Nasution, Nursanita; Hasibuan, Wulan; Hutagalung, Nuraisyah Dera; Kesuma, Aldimas Maulana; Sitorus, Rezky Alya Mawaddah; Sembiring, Wira Anjani Br; Wasiyem, Wasiyem (PROMOTOR, 2025)
The World Health Organization (WHO) noted that Indonesia is included in the list of countries with the highest TB burden in the world, with significant incidence in various age groups and socio-economic. TB spreads through the air, especially when people cough, sneeze, talk, or spit out, which secrete small droplets containing bacteria. This article aims to provide a more detailed overview of the prevalence of TB in Martubung Village, as well as present data that can be used as a reference in designing effective disease control strategies. The research method using the descriptive quantitative research method is an approach that aims to describe or describe phenomena that occur in the field based on the data obtained. This study uses numerical data processed by statistical means to get a clearer picture of the phenomenon being studied. The results of the study showed that from a survey conducted on 35 respondents, it was found that 6 of them were confirmed to have Tuberculosis (TB), which means 17.14% of the total respondents. One of the TB cases led to death, so that the fatality rate in this group reached 16.67%. Although this number is not very high, it still shows that tuberculosis can be fatal if not treated properly. The conclusion of this study shows the importance of increasing public awareness about the symptoms, modes of transmission, and the importance of early treatment to reduce the incidence and mortality rate due to TB.